The Treatment Of Secondary Malocclusıon In Patıents Wıth Perıodontal Dısease - Sönmez Arıcan; Erhan Fıratlı; Türköz Uğur (Galenos Yayinevi, 1989)
The loss of osseous support resulting from periodontal disease is an setiological factor in the development of secondary malocclusions. Correction of these malocclusions demand a) advanced techniques, b) an understanding of the biological situation present in the patient with periodontal disease and c) adaptation of these techniques and forces to the reduced support. According to the treatment of malocclusion there are improvements in plaque accumulation and the distribution of occlusal forces. These factors, maintain the long term health of the teeth and their periodontium. These kind of treatment requires the maximum interdisciplinary collaboration.